2009
DOI: 10.1007/s12282-009-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon case of T1b breast cancer with diabetic mastopathy in type II diabetes mellitus

Abstract: A 64-year-old postmenopausal female had been treated with insulin therapy for type 2 diabetes mellitus for 18 years, but her diabetes mellitus was not well controlled and she developed retinopathy. Her screening mammography showed abnormal findings, and thus she consulted a hospital. A physical examination showed her mammary glands to be hard on both sides and no palpable mass was observed. Mammography revealed an amorphous calcification in the middle outer portion of the left breast. Ultrasonography showed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A retrieved case reporting suspected microcalcifications was associated with intra ductal carcinoma. [9] Ultrasonography is more sensitive than mammography to detect in our case a heterogeneous mass classified BIRADS 4, which presented according to the criteria of classification BI-RADS 2013, an irregular shape, an orientation parallel to the cutaneous plane with uncircumscribed contours and attenuation of the ultrasound beam. This description was notified in most of the clinical cases described in the literature [10,11] and in the series of Moschetta et al (77%), [12] by Kim et al (69%).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A retrieved case reporting suspected microcalcifications was associated with intra ductal carcinoma. [9] Ultrasonography is more sensitive than mammography to detect in our case a heterogeneous mass classified BIRADS 4, which presented according to the criteria of classification BI-RADS 2013, an irregular shape, an orientation parallel to the cutaneous plane with uncircumscribed contours and attenuation of the ultrasound beam. This description was notified in most of the clinical cases described in the literature [10,11] and in the series of Moschetta et al (77%), [12] by Kim et al (69%).…”
Section: Discussionmentioning
confidence: 66%
“…[10] It has also been highlighted in literature, the coexistence of breast cancer with diabetic mastopathy. [9] Therefore, it seems necessary to always take biopsies in a diabetic patient before a mass classified BIRADS 4 more or less associated with suspicious micro calcifications or having a family history of breast cancer. The management of this pathology involved for several case radical surgery lesions with a significant risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement of imaging techniques, there are still great challenges in the diagnosis of diabetic breast disease[ 9 , 21 - 23 ]. An increasing number of studies have reported cases of diabetic breast disease complicated with malignant tumors[ 24 , 25 ], and some studies[ 26 , 27 ] have also shown that neither clinical examination nor imaging studies can clearly distinguish diabetic breast disease from breast cancer. Therefore, the diagnosis of this disease needs improvement and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…The medical literature contains four case reports documenting instances where DMP and ductal carcinoma coexist in the same breast [2831]. This reinforces the need for exhaustive clinicopathological evaluation and a high index of suspicion.…”
Section: Discussionmentioning
confidence: 99%